Some Oil Presses from Western Galilee - Frankel, Rafael (Bulletin of ASOR, 1992)
Five oil presses from the Roman and Byzantine periods excavated in western Galilee are described and related to data from an archaeological survey of the region. Mapping the distribution areas of the various types of press components makes it possible to define the types of presses characteristic of the region. The presses belong to types found only in a clearly demarcated zone that can be equated with the extreme southern area of Phoenicia. The Phoenician presses differ in many ways from those found in other regions of Israel. In the Phoenician lever-and-weights press the beam is anchored between slotted piers and the oil collection is lateral, as opposed to the Judaean lever-and-weights press, in which the beam is anchored in a niche in the wall and the oil is collected in a central vat with plain piers on either side. The Phoenician lever-and-screw press differs from the characteristic Judaean direct pressure grooved-pier screw press. The types of screw weights found in the northern lever-and-screw press also differ from those found in the central regions of the country-Samaria, Sharon, and Carmel. The Phoenician screw weights apparently are an internal development of the region. Many of the regional characteristics originated in earlier periods, and continued, and in some cases still appeared in preindustrial installations.